2014
DOI: 10.1016/j.bbagrm.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Exon 9 skipping of apoptotic caspase-2 pre-mRNA is promoted by SRSF3 through interaction with exon 8

Abstract: Alternative splicing plays an important role in gene expression by producing different proteins from a gene. Caspase-2 pre-mRNA produces anti-apoptotic Casp-2S and proapoptotic Casp-2L proteins through exon 9 inclusion or skipping. However, the molecular mechanisms of exon 9 splicing are not well understood. Here we show that knockdown of SRp20 with siRNA induced significant increase of endogenous exon 9 inclusion. In addition, overexpression of SRp20 promoted exon 9 skipping. Thus we conclude that SRp20 promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 39 publications
(39 reference statements)
2
34
0
Order By: Relevance
“…27 Another interesting possibility is that the binding sites within exon 15 may also control the splicing of exon 16, as SRSF3 has been shown in Caspase2 mRNA to cause the skipping of an exon (exon 9) by binding to ESS in an upstream exon (exon 8). 28 Therefore SRSF3 may promote the proximal splice site selection and inhibit distal splice site selection.…”
Section: Discussionmentioning
confidence: 99%
“…27 Another interesting possibility is that the binding sites within exon 15 may also control the splicing of exon 16, as SRSF3 has been shown in Caspase2 mRNA to cause the skipping of an exon (exon 9) by binding to ESS in an upstream exon (exon 8). 28 Therefore SRSF3 may promote the proximal splice site selection and inhibit distal splice site selection.…”
Section: Discussionmentioning
confidence: 99%
“…SRSF3 reportedly modulated the alternative splicing of several apoptosis-related genes, such as caspase-2 ( Casp2 ), programmed cell death 4 ( PDCD4 ), and homeodomain-interacting protein kinase-2 ( HIPK2 ) in distinct cancer cells [109,110,111]. Caspase-2 was demonstrated to act the early initiator in the intrinsic apoptosis pathway [112].…”
Section: Impacts Of Alternative Splicing Events On Apoptosismentioning
confidence: 99%
“…Intriguingly, the sequencing of this band confirmed an exon 5 skipping. This event could be consistent with the inactivation of the ESEs placed on the adjacent exon . It is suggested that the SRSF2 protein would be regulating exon 5 inclusion through its interaction with the ESEs placed on exon 6.…”
Section: Discussionmentioning
confidence: 58%